2011
DOI: 10.5665/sleep.1138
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Insomnia in the Ibadan Study of Ageing

Abstract: There is a high incidence and chronicity of insomnia in this elderly population. Persons with chronic health conditions are particularly at risk of new onset as well as persistence of insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 28 publications
4
56
2
4
Order By: Relevance
“…Female gender 19, 23, 25-29 , depressed mood 19, 20, 24, 26-29 and poor physical health 21-24, 26-29 were most consistently reported as independent predictors of these sleep outcomes. Four studies examined physical activity with mixed findings (see discussion) 20, 21, 24, 30 .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Female gender 19, 23, 25-29 , depressed mood 19, 20, 24, 26-29 and poor physical health 21-24, 26-29 were most consistently reported as independent predictors of these sleep outcomes. Four studies examined physical activity with mixed findings (see discussion) 20, 21, 24, 30 .…”
Section: Resultsmentioning
confidence: 94%
“…Independent estimates of the effects of age were reported in the minority of these studies (5/13) 20, 21, 23, 27, 28 , in two cases presumably due to the fact that age was not associated with future sleep disturbance in univariate analyses 19, 25 . Of the studies examining the adjusted effect of age, one identified increased risk for older (75+ years) adults 18 , while another study found significantly increased risk for incident insomnia symptoms for white, but not black adults aged 75-84 27 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies include a population study assessing participants approximately 7 years after baseline in which, relative to good sleepers, persistently poor sleepers (with insomnia complaints, but not primary insomnia) were more likely to develop chronic insomnia and that this was associated with physical and mental health conditions, female sex, but not older age [35]. In a unique sample, community dwelling older adults in Africa, lower socioeconomic standing and chronic health conditions were significant factors for predicting the incidence of insomnia, whereas age and sex were not [36]. Compelling data from a 20-year longitudinal study of two different age cohorts (middle-aged and older adults) underscore the role of age and female sex, as well as manual rather than nonmanual occupations, in the development of chronic insomnia [37].…”
Section: The Natural History Of Insomniamentioning
confidence: 86%